Training defensive high-press in soccer: physical and physiological responses to different small-sided games played by youth athletes - de Oliveira Abreu, C.; Perez Morales, J. C.; Greco, P. J.; Praca, G. M. (International Journal of Performance Analysis in Sport, 2023)
This analysed the impact of high-press oriented rules during soccer small-sided games on players` physical and physiological responses and to analyse whether integrating multiple informational constraints - rules - would increase the effect compared to the control game. Thirty-two U-20 elite soccer players engaged in this study. All players engaged in all the four conditions: control (no additional rules), 1-rule games (A, in which the defending team scores two points every time they regained the ball possession in their offensive midfield, and B, in which the attacking team scores two points every time they achieve a shot on goal in their offensive midfield), and 2-rules game (integrating both rules A and B) in random and balanced order. Physical and physiological variables were collected through a GPS device and a chest strap. A MANOVA was adopted to analyse the main effect of protocol on players` responses. Results indicated that 1-rule games presented higher physical and physiological demands. In addition, high-press games elicited higher physiological and physical responses than free-play. Combining rules decreased the physical and physiological responses compared to applying the rules separately.